Present to Anyone on Any Devices? The Conflict Between Telework and Family Life for Teachers and Researchers of Helping Professions - Emese Beáta Berei (Central European Journal of Educational Research)
The study examined the digital work experiences of academics in human services professions (teachers, doctors, health workers, and clergy). Answers to the following question were sought after: What are the patterns related to digital work? How does work-life or family conflict (WLC) affect teleworking? It was hypothesized that digital work generates WLC. Quantitative international data were collected by the Research and Development Centre for Higher Education (CHERD–H) at the University of Debrecen in 2023, across five countries (Romania, Slovakia, Hungary, Serbia, and Ukraine). A subsample of 315 academics involved in caring professions was collected and principal component analysis, ANOVA, and correlation tests were performed using the SPSS statistical program. The subsample included 114 male and 193 female teachers, 33 of whom were Romanian. Perceptions of advantages and disadvantages dominated the digital work patterns. In addition, a "digital super-power" component was identified. The ANOVA test showed that Romanian academics had a significantly higher average in perceiving disadvantages compared to others. Academics working minimal hours were considerably more open to seeing the benefits of digital technology than those with longer working hours. According to the correlation test results, there was a negative relationship between the level of WLC and the perception of technology benefits: those who detected digital advantages had lower WLC values, while those who recognized disadvantages had higher WLC values.